Preparation method of high-entropy layered double hydroxide with strong strain effect
By preparing a five-member high-entropy layered double hydroxide catalyst, the technical gap of five-member high-entropy LDH material in activates PMS to degrade water pollutants is solved, and the efficient tetracycline degradation effect is achieved, and the catalytic performance is maintained for a long time. .
Patent Information
- Application Number
- CN202411651377.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
AI Technical Summary
There is currently a lack of technology to apply five-membered high-entropy layered double hydroxide (LDH) materials to activate permonosulphate-based advanced oxidation processes (PMS-AOPs) to degrade water pollutants.
By dissolving iron salts, cobalt salts, nickel salts, copper salts and zinc salts in water, preparing a mixed salt solution, and adding alkaline aqueous solution of sodium hydroxide and sodium carbonate to form a yellowish-brown floc precipitate, followed by water heat The reaction was heated in the kettle, and centrifuged, washing and freeze-dried, and finally a five-membered high-entropy layered double hydroxide catalyst was obtained.
The prepared high-entropy FeCoNiCuZn-LDH catalyst can exhibit 90% tetracycline degradation efficiency within 3 minutes, have a strong strain effect, enhance the adsorption energy of the catalyst active site, lengthen the O-O bond length in PMS, and after multiple cycles Performance can still reach more than 90%.
Smart Images

Figure CN119461517A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic functional materials, and in particular relates to a high entropy layered double hydroxide with a strong strain effect, and a preparation method and application thereof. Background Art
[0002] High entropy materials (HEMs) have attracted great interest in the materials science community due to their unique structural features and beneficial properties such as structural stability, abundant active sites, and tailorable composition. These materials are known for inducing ultradense lattice distortions, which can lead to various strains. In recent years, there has been increasing interest in understanding the strain effects in catalytic processes, which arise from structural defects such as atomic spacing changes, lattice mismatch, and microstrain or local lattice distortion. These factors significantly enhance the chemical and electronic structures of metallic systems, thereby optimizing the catalytic performance of nanomaterials.
[0003] At present, the research on HEMs includes structures such as calcite, spinel, hydrotalcite and fluorite, all of which contain multiple metal elements. Among them, layered double hydroxides (LDH) are known for the flexibility, uniform distribution, abundant surface hydroxyl groups and highly dispersed metal active centers of their interlayer metal cations. Therefore, multi-component LDH catalysts ranging from ternary and quaternary (medium entropy) to quinary (high entropy) compositions have emerged. Compared with single-component LDH materials, the catalytic performance of these multi-component LDH materials is particularly outstanding.
[0004] The momentum for using multi-component LDH catalytic materials to solve global water pollution problems has been quite strong, especially with the emergence of peroxymonosulfate-based advanced oxidation processes (PMS-AOPs) for the degradation of water pollutants. Among them, the activated peroxymonosulfate-based advanced oxidation process is particularly popular due to its SO4· - Free radicals have the advantages of higher redox potential (2.5-3.1V) and longer half-life (30-40μs) in a wide pH range, and are considered to be a practical and convenient method for removing residual antibiotics such as tetracycline in water. In addition, PMS can also be rapidly converted into various reactive oxygen species (ROS) (SO4· - , ·OH, 1 O2 and O2 - ). Secondly, the direct synthesis and adjustable multi-metal active centers of LDH materials make them increasingly attractive for PMS-AOPs applications. Although binary and ternary LDH catalytic materials have been widely studied in PMS activation for pollutant degradation, pentad high-entropy LDH materials have not been applied to activate PMS for degradation of water pollutants. Therefore, combining multifunctional LDH materials with high-entropy driven strain effects is expected to obtain highly effective catalytic materials in the field of advanced oxidation. Summary of the invention
[0005] In view of this, in order to solve the above technical problems, a high entropy layered double hydroxide with strong strain effect and a preparation method and application thereof include the following steps:
[0006] Step 1, dissolving iron salt, cobalt salt, nickel salt, copper salt and zinc salt in water, and preparing a mixed salt solution of iron, cobalt, nickel, copper and zinc under stirring;
[0007] Step 2, dissolving sodium hydroxide and sodium carbonate in water, and preparing an alkali source aqueous solution under stirring;
[0008] Step 3, adding an alkali source aqueous solution to the mixed salt solution of iron, cobalt, nickel, copper and zinc under stirring to form a yellow-brown flocculent precipitate;
[0009] Step 4, transferring the yellow-brown flocculent precipitate prepared in step 3 to a hydrothermal kettle, and then heating in an oven for reaction; the precipitate after the reaction is centrifuged and washed three times with deionized water and three times with anhydrous ethanol to obtain a dark brown precipitate;
[0010] Step 5: freeze-dry the dark brown precipitate prepared in step 4 to obtain a five-membered high entropy layered double hydroxide catalyst.
[0011] Further, the concentrations of the iron salt, cobalt salt, nickel salt, copper salt and zinc salt solutions in step 1 are all 0.1-0.2 mol / L. Further, the iron salt in step 1 is one or more of ferric nitrate, ferric chloride, ferric sulfate or ferric acetate, the cobalt salt is one or more of cobalt nitrate, cobalt chloride, cobalt sulfate or cobalt acetate, the nickel salt is one or more of nickel nitrate, nickel chloride, nickel sulfate or nickel acetate, the copper salt is one or more of copper nitrate, copper chloride, copper sulfate or copper acetate, and the zinc salt is one or more of zinc nitrate, zinc chloride, zinc sulfate or zinc acetate; the molar ratio of the iron salt, cobalt salt, nickel salt, copper salt and zinc salt is 0.6:1:1:1:1-1:1:1:1:1:1.
[0012] Furthermore, the stirring conditions in steps 1-3 are a temperature of 20-25° C. and a rotation speed of 180-220 r / min.
[0013] Furthermore, the molar ratio of sodium carbonate to sodium hydroxide in step 2 is 1:2-1:5; the volume ratio of the mixed salt solution of iron, cobalt, nickel, copper and zinc to the alkaline source aqueous solution is 1:1-4:1.
[0014] Further, the reaction temperature in steps 1-3 is 15-30°C.
[0015] Furthermore, the hydrothermal reaction temperature in step 4 is 40-150° C., and the reaction time is 12-72 hours.
[0016] Furthermore, the freeze-drying time in step 5 is 12-72 hours.
[0017] The invention also discloses a high entropy layered double hydroxide catalyst with a strong strain effect prepared by the above preparation method.
[0018] Compared with the prior art, the present invention can achieve the following technical effects:
[0019] (1) The preparation process of the present invention is simple and has high production efficiency. The product is obtained by simply mixing the metal salt and the alkali source and then transferring them to a hydrothermal reactor for reaction.
[0020] (2) The high entropy FeCoNiCuZn-LDH catalyst prepared before the present invention activated PMS to degrade pollutants in water, showing 90% TC degradation within 3 minutes.
[0021] (3) The high entropy FeCoNiCuZn-LDH catalyst prepared by the present invention has a strong strain effect, which enhances the adsorption energy of the active sites of the catalyst and lengthens the bond length of OO in PMS.
[0022] (4) The performance of the high entropy FeCoNiCuZn-LDH catalyst prepared by the present invention can still reach more than 90% after multiple cycles. Of course, any product implementing the present invention does not necessarily need to achieve all the above-mentioned technical effects at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0024] Figure 1 This is a TEM photograph of the high entropy layered double hydroxide catalyst prepared in Example 1 of the present invention.
[0025] Figure 2 This is a GPA stress analysis diagram of the high entropy layered double hydroxide catalyst prepared in Example 1 of the present invention.
[0026] Figure 3 This is the XRD diagram of the high entropy layered double hydroxide catalyst prepared in Example 1 of the present invention.
[0027] Figure 4 This is a graph of TC removal rate of the high entropy layered double hydroxide catalyst prepared in Example 1 of the present invention.
[0028] Figure 5 This is a calculated simulation diagram of the adsorption energy of the main metal active sites of the high entropy layered double hydroxide catalyst prepared in Example 1 of the present invention and the change of the OO bond of PMS.
[0029] Figure 6 This is a theoretical calculation diagram of the degradation rate of the high entropy layered double hydroxide catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The following will describe the implementation methods of the present invention in detail with reference to the embodiments, so that the implementation process of how the present invention applies technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.
[0031] The present application discloses a high entropy layered double hydroxide with a strong strain effect and a preparation method and application thereof, comprising the following steps:
[0032] Step 1, dissolving iron salt, cobalt salt, nickel salt, copper salt and zinc salt in water, and preparing a mixed salt solution of iron, cobalt, nickel, copper and zinc under stirring;
[0033] Step 2, dissolving sodium hydroxide and sodium carbonate in water, and preparing an alkali source aqueous solution under stirring;
[0034] Step 3, adding an alkali source aqueous solution to the mixed salt solution of iron, cobalt, nickel, copper and zinc under stirring to form a yellow-brown flocculent precipitate;
[0035] Step 4, transferring the yellow-brown flocculent precipitate prepared in step 3 to a hydrothermal kettle, and then heating in an oven for reaction; the precipitate after the reaction is centrifuged and washed three times with deionized water and three times with anhydrous ethanol to obtain a dark brown precipitate;
[0036] Step 5: freeze-dry the dark brown precipitate prepared in step 4 to obtain a five-membered high entropy layered double hydroxide catalyst.
[0037] In this preparation method
[0038] 1. Add a certain amount of sodium hydroxide and sodium carbonate alkali source aqueous solution to the mixed salt solution of iron, cobalt, nickel, copper and zinc. The alkali source aqueous solution provides the necessary hydroxyl groups to form the LDH structure, and at the same time regulates the pH of the solution, which is conducive to the formation of LDH structure with higher concentrations of ligand hydroxyl groups and iron, cobalt, nickel, copper and zinc ions. If the volume of the added alkali source aqueous solution is not proportional to the volume of the mixed salt solution, the mixed salt of iron, cobalt, nickel, copper and zinc will easily directly form the corresponding individual hydroxides, and the LDH structure cannot be obtained.
[0039] 2. By controlling the full reaction in the hydrothermal reactor under certain temperature conditions, the LDH crystal structure of the high entropy layered double hydroxide is more significant and free of impurities.
[0040] Example 1
[0041] Dissolve ferric nitrate, cobalt nitrate, nickel nitrate, copper nitrate and zinc nitrate in deionized water to prepare 20 mL of a mixed salt solution containing 0.06 mol / L ferric nitrate, 0.1 mol / L cobalt nitrate, 0.1 mol / L nickel nitrate, 0.1 mol / L copper nitrate and 0.1 mol / L zinc nitrate. At the same time, prepare 20 mL of an alkali source aqueous solution containing 1 mol / L sodium carbonate and 2 mol / L sodium hydroxide, respectively. Mix the mixed salt solution with the alkali source aqueous solution under stirring conditions of 200 r / min and 25°C. After the appearance of yellow-brown floccules, transfer to a hydrothermal autoclave at 60°C to react for 12 hours. After the reaction, the flocculent precipitate is centrifuged, washed three times with deionized water, washed three times with anhydrous ethanol, and transferred to a freeze-drying instrument for 24 hours to obtain a brown solid powder product, i.e., a five-element high-entropy layered double hydroxide catalyst. The transmission electron micrograph of the obtained sample is shown in Figure 1 As shown in Figure 2, it can be seen that the prepared sample is a sheet-like structure with uniform morphology, and its XRD spectrum is as follows: Figure 2 As shown, the positions of all diffraction peaks are the same as those of the standard card CoFe-LDH (PDF#50-0235), indicating the successful preparation of layered double hydroxide. The high entropy configuration was mainly determined by calculating the molar mixing entropy. mix Materials with R ≥ 1.5 are classified as high entropy materials (R = 8.314 J / mol / K, universal gas constant). Figure 3 The EDS and the molar ratio data of the ICP metal phase in Table 1 show the presence of five metal elements in the material. The mixing entropy of the prepared sample calculated from the data in Table 1 reached 13.14 (1.58R≥1.5R), and the molar ratio of the five metal elements was close to 1:1:1:1:1, confirming the high entropy property of the sample. Figure 4 The GPA stress analysis graph shown in the figure shows that the sample exhibits xx and ε yy The performance of the prepared high entropy layered double hydroxide catalyst for activating PMS to degrade tetracycline is shown in Figure 5 As shown in the figure, under normal temperature and pressure, the reaction time is 10 minutes. The degradation rate of tetracycline is as high as 97%. Figure 6 As shown in the figure, its excellent degradation efficiency comes from the strong strain effect of the catalyst on the adsorption energy and the elongation of OO in PMS, which promotes the generation of more reactive free radicals.
[0042] Table 1 is a table of molar ratios of ICP metal elements of the high entropy layered double hydroxide catalyst prepared in Example 1 of the present invention.
[0043]
[0044] Table 1 Metal element molar ratio of Fe-Co-Ni-Cu-Zn-LDH samples
[0045] Example 2
[0046] The method comprises dissolving ferrous sulfate, cobalt sulfate, nickel sulfate, copper sulfate and zinc sulfate in deionized water, preparing 40 mL of a mixed salt solution containing 0.1 mol / L ferrous sulfate, 0.12 mol / L cobalt sulfate, 0.12 mol / L nickel sulfate, 0.12 mol / L copper sulfate and 0.12 mol / L zinc sulfate, and preparing 20 mL of an alkali source aqueous solution containing 2 mol / L sodium carbonate and 8 mol / L sodium hydroxide, respectively. After a yellow-brown flocculent appears, the solution is transferred to a hydrothermal autoclave at a temperature of 70° C. and reacted for 24 hours. The flocculent precipitate after the reaction is centrifuged, washed three times with deionized water, washed three times with anhydrous ethanol, and transferred to a freeze drying apparatus and dried for 36 hours to obtain a brown solid powder product, i.e., a five-element high-entropy layered double hydroxide catalyst.
[0047] Example 3
[0048] Ferric chloride, cobalt chloride, nickel chloride, copper chloride and zinc chloride are dissolved in deionized water to prepare 60 mL of a mixed salt solution containing 0.12 mol / L ferric chloride, 0.16 mol / L cobalt chloride, 0.16 mol / L nickel chloride, 0.16 mol / L copper chloride and 0.16 mol / L zinc chloride, and 20 mL of an alkali source aqueous solution containing 3 mol / L sodium carbonate and 9 mol / L sodium hydroxide, respectively, are prepared at the same time. After a yellow-brown flocculent appears, the mixture is transferred to a hydrothermal autoclave at a temperature of 80° C. and reacted for 48 hours. The flocculent precipitate after the reaction is centrifuged, washed three times with deionized water, washed three times with anhydrous ethanol, and transferred to a freeze drying apparatus and dried for 48 hours to obtain a brown solid powder product, i.e., a five-element high-entropy layered double hydroxide catalyst.
[0049] Example 4
[0050] Ferrous acetate, cobalt acetate, nickel acetate, copper acetate and zinc acetate are dissolved in deionized water to prepare 80 mL of a mixed salt solution containing 0.16 mol / L ferrous acetate, 0.2 mol / L cobalt acetate, 0.2 mol / L nickel acetate, 0.2 mol / L copper acetate and 0.2 mol / L zinc acetate, and 20 mL of an alkali source aqueous solution containing 4 mol / L sodium carbonate and 16 mol / L sodium hydroxide, respectively, are prepared at the same time. After a yellow-brown flocculent appears, the mixture is transferred to a hydrothermal autoclave at a temperature of 90° C. and reacted for 72 hours. The flocculent precipitate after the reaction is centrifuged, washed three times with deionized water, washed three times with anhydrous ethanol, and transferred to a freeze drying apparatus and dried for 72 hours to obtain a brown solid powder product, i.e., a five-element high-entropy layered double hydroxide catalyst.
[0051] The above description shows and describes several preferred embodiments of the invention, but as mentioned above, it should be understood that the invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept described herein through the above teachings or the technology or knowledge of the relevant field. Changes and modifications made by those skilled in the art should be within the scope of protection of the claims attached to the invention without departing from the spirit and scope of the invention.
Claims
1. A method for preparing a high entropy layered double hydroxide with a strong strain effect, comprising the following steps: Step 1, dissolving iron salt, cobalt salt, nickel salt, copper salt and zinc salt in water, and preparing a mixed salt solution of iron, cobalt, nickel, copper and zinc under stirring; Step 2, dissolving sodium hydroxide and sodium carbonate in water, and preparing an alkali source aqueous solution under stirring; Step 3, adding an alkali source aqueous solution to the mixed salt solution of iron, cobalt, nickel, copper and zinc under stirring to form a yellow-brown flocculent precipitate; Step 4, transferring the yellow-brown flocculent precipitate prepared in step 3 to a polytetrafluoroethylene reactor, and then heating the reaction in an oven; the precipitate after the reaction is centrifuged, washed three times with deionized water, and washed three times with anhydrous ethanol to obtain a dark brown precipitate; Step 5: freeze-dry the dark brown precipitate prepared in step 4 to obtain a five-membered high entropy layered double hydroxide catalyst.
2. The method for preparing a high entropy layered double hydroxide with a strong strain effect according to claim 1, characterized in that: The concentrations of the iron salt, cobalt salt, nickel salt, copper salt and zinc salt solutions in step 1 are all 0.1-0.2 mol / L.
3. The method for preparing a high entropy layered double hydroxide with a strong strain effect according to claim 1, characterized in that: The iron salt in the step 1 is one or more of iron nitrate, iron chloride, iron sulfate or iron acetate, the cobalt salt is one or more of cobalt nitrate, cobalt chloride, cobalt sulfate or cobalt acetate, the nickel salt is one or more of nickel nitrate, nickel chloride, nickel sulfate or nickel acetate, the copper salt is one or more of copper nitrate, copper chloride, copper sulfate or copper acetate, and the zinc salt is one or more of zinc nitrate, zinc chloride, zinc sulfate or zinc acetate; the molar ratio of the iron salt, the cobalt salt, the nickel salt, the copper salt and the zinc salt is 0.6:1:1:1:1-1:1:1:1:
1.
4. The method for preparing a high entropy layered double hydroxide with a strong strain effect according to claim 1, characterized in that The stirring conditions in steps 1-3 are a temperature of 20-25° C. and a rotation speed of 180-220 r / min.
5. The preparation method according to claim 1, characterized in that: The molar ratio of sodium carbonate to sodium hydroxide is 1:2-1:5; the volume ratio of the mixed salt solution of iron, cobalt, nickel, copper and zinc to the alkali source aqueous solution is 1:1-4:
1.
6. The method for preparing a high entropy layered double hydroxide with a strong strain effect according to claim 1, characterized in that: The reaction temperature in steps 1-3 is 15-30°C.
7. The method for preparing a high entropy layered double hydroxide with a strong strain effect according to claim 1, characterized in that: The hydrothermal reaction vessel reaction temperature in step 4 is 40-150° C., and the reaction time is 12-72 hours.
8. The method for preparing a high entropy layered double hydroxide with a strong strain effect according to claim 1, characterized in that: The freeze drying time in step 4 is 12-72 hours.
Citation Information
Cited By
High-entropy layered metal hydroxide composite material as well as preparation method and flame-retardant and smoke-suppression application thereof
CN120058006A
A high-entropy layered metal hydroxide composite material, a preparation method thereof and a flame-retardant and smoke-suppressing application thereof
CN120058006B
High-entropy layered double hydroxide electrode material, preparation method and application thereof
CN122166895A